2020
DOI: 10.1021/acs.cgd.9b01669
|View full text |Cite
|
Sign up to set email alerts
|

p-Type Ultrawide-Band-Gap Spinel ZnGa2O4: New Perspectives for Energy Electronics

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 69 publications
(126 reference statements)
9
57
0
Order By: Relevance
“…Recently, Chikoidze et al [7] demonstrated that spinel ZnGa 2 O 4 is the native p-type ternary oxide semiconductor with the widest bandgap. Their work has extended to cover the bipolar mechanisms in optoelectronics and power electronics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Chikoidze et al [7] demonstrated that spinel ZnGa 2 O 4 is the native p-type ternary oxide semiconductor with the widest bandgap. Their work has extended to cover the bipolar mechanisms in optoelectronics and power electronics.…”
Section: Discussionmentioning
confidence: 99%
“…This wide-bandgap material is attracting significant attention due to the possibility of its use not only in high-powered devices, but also in UV-transparent devices-especially for applications in conjunction with biological samples-because absorption peaks in deoxyribonucleic acid (DNA) lie in the UV spectrum [6]. Recently, Chikoidze et al demonstrated the p-type ZnGa 2 O 4 semiconductor (∼5 eV), which can pave the way for bipolar oxide energy electronics (it can save the loss from switching and conversion of electrical energy), as they would join the required qualities of sustaining large electrical fields in p-n junctions in the off-state together with low losses in the on-state [7]. Besides this, wide-bandgap semiconductors enhance the efficiency of power-conversion stages and these are an alternative for silicon in the manufacturing of voltage converters, power MOSFETs, and high-efficiency Schottky diodes, which can be further used in electric vehicles and hybrid electric vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Agnitron Technology Incorporated (USA) reported β-Ga2O3 Zn doped thin films on c-sapphire by MOCVD the incorporation of 10.9% Zn XRD patterns yielded to a mono-phase polycrystalline structure with increase of lattice parameters with doping, though room temperature Hall measurements were not successful due to very high resistivity of the samples [27]. Recently, we have shown that incorporation of Zn in p-type β-Ga2O3 with more than 5% leads the transformation of orthorhombic structure into spinel ZnGa2O4 with an increased band gap (~0.2 eV) and p-type carrier densities (×10-100 cm -3 ) [28]. Very few experimental works are reported about low doping cases, when incorporated Zn amount is less than 1%.…”
Section: Intrinsic and Zn-doped P-type Ga2o3 A Reviewmentioning
confidence: 99%
“…[106][107][108] Furthermore, wide band-gap materials can be applied as UV optoelectronics and UV-transparent devices, emerging as a potential candidate for applications in different fields. [109,110]…”
Section: Structural Parametersmentioning
confidence: 99%